Concomitant exposure to benzodiazepines during pembrolizumab-based therapy for advanced non-small-cell lung cancer: a propensity-score matched analysis of monitoring agency data - Fabrizio Nelli; Enzo Maria Ruggeri; Antonella Virtuoso; Diana Giannarelli; Armando Raso; Federica Natoni; Gloria Pessina; Daniele Remotti; Mario Giovanni Chilelli; Carlo Signorelli; Agnese Fabbri (Exploration of Targeted Anti-tumor Therapy)
Aim: The interaction of concomitant benzodiazepine (BZD) exposure during immune checkpoint blockade has not been comprehensively investigated to date. This research aimed to determine the influence of BZD intake on the survival outcomes of patients with metastatic non-small-cell lung cancer (NSCLC) receiving pembrolizumab-based therapies. Methods: We included consecutive patients with advanced NSCLC who were given frontline pembrolizumab, whether as exclusive therapy or combined with platinum-based chemotherapy. The classification of BZD relied on the molecular composition, distinguishing between N-substituted and N-unsubstituted compounds. Results: During the time frame from April 2018 to May 2023, we enrolled 258 patients, 156 (60.5%) and 102 (39.5%) of whom received pembrolizumab alone or the combination regimen, respectively. We identified 108 (41.8%) exposed patients (BZD cohort) in comparison to all others (no-BZD cohort). After applying propensity-score matching, 108 cases were relevant for each cohort. After a median follow-up of 16.3 [95% confidence interval (CI) 13.1–19.7] months, univariate analysis revealed no significant differences in terms of progression-free survival (PFS) or overall survival (OS) between BZD cohorts. However, patients exposed to N-substituted compounds had significantly longer PFS and OS than those who did not take BZD. Conversely, patients exposed to N-unsubstituted compounds experienced significantly shortened OS. Multivariate testing showed that taking unspecified BZD had no impact on PFS or OS, while N-substituted BZD exposure correlated independently with longer PFS [hazard ratio (HR) 0.52 (95% CI 0.34–0.79); P = 0.002] and OS [HR 0.58 (95% CI 0.38–0.88); P < 0.001]. In contrast, N-unsubstituted BZD intake had worsening effects on OS [HR 1.92 (95% CI 1.20–3.06); P = 0.006]. Conclusions: BZD exposure may impact the efficacy of immune checkpoint inhibitors in patients with advanced NSCLC. The specific composition may influence the choice among different compounds.